The Justice Syndicate: using iPads to increase the intensity of participation, conduct agency and encourage flow in live interactive performance. Issue 1 (2nd January 2020) - Barnard, Daniel; De Meyer, Kris
ABSTRACT: The Justice Syndicate is an interactive performance, featuring an audience who take on the role of jurors considering a difficult case. Participants receive evidence, witness testimonies and prompts to vote and discuss the case on iPads. With this practice-as-research project we explored what are the most effective means of inviting people to participate; how to widen their 'horizon of participation'; how to heighten the intensity of interaction in order to increase the level of 'agentive behaviour' of the participants; and how to create a sense of Flow in participants. We found that an effective solution to the fear of experiencing or causing embarrassment is for the invitation to participate to come from a machine and for there to be no distinction between 'audience' and 'participants'. This also proved an effective way of stimulating a high intensity of 'agentive behaviour' among audience members, although it did not automatically lead to a greater feeling of agency. Applying an adapted version of Lindinger and colleagues' [(2013). "The (St)Age of Participation: Audience Involvement in Interactive Performances." Digital Creativity 24 (2): 119–129. doi:10.1080/14626268.2013.808966] codification of how to stimulate a state of Flow in audience members also proved effective in creating a highly immersive experience.